Upaya Pemulihan Sektor Pariwisata di Desa Gubugklakah Pasca Pandemi Covid-19 - Medita Wilda Wulandari; Melly Indrawati; Ummi Nazla Maghfiroh P.; Slamet Fauzan (Jurnal Abdimas Pariwisata, 2022)
Efforts to Restore the Tourism Sector in Gubugklakah Village After the Covid-19 Pandemic. The tourism sector is a contributor to state revenue in the form of foreign exchange and plays a role in increasing productivity and reducing unemployment. The Covid-19 pandemic has caused the tourism sector to be paralyzed and dead so that it cannot contribute to the economy. Gubugklakah Village is one of the tourist villages affected by Covid-19. The village of Gubugklakah, which is usually busy with tourists, has become deserted, this causes a decrease in the income of the local community. The methods used in this service include observation, interviews, group discussion forums, documentation, and publications. This service activity can be called tourism branding, which is the method of choice as an effort to restore the post-pandemic tourism sector in Gubugklakah Village. Tourism branding can be done by utilizing existing social media such as Instagram, Tiktok, Youtube, and Facebook. Social media is expected to be able to reach local and foreign tourists, by disseminating information about existing tourism so that the local community's economy will come back to life. In line with the purpose of the activity, local tourists have started to arrive who want to travel in Gubugklakah Village.